2011
DOI: 10.1111/j.1365-2966.2011.18441.x
|View full text |Cite
|
Sign up to set email alerts
|

Instabilities, nulls and subpulse drift in radio pulsars

Abstract: This paper continues a previous study of neutron stars with positive polar‐cap corotational charge density in which free emission of ions maintains the surface electric field boundary condition E·B= 0. The composition of the accelerated plasma on any subset of open magnetic flux lines above the polar cap alternates between two states: protons or positrons and ions, of which the proton state cannot support electron–positron pair creation at higher altitudes. The two states coexist at any instant of time above d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…The ansatz for this paper is consistent with similar ideas expressed by other authors (Ruderman & Sutherland 1975;Cordes 1979Cordes , 1983Jones 1982Jones , 1986Jones , 2011Timokhin 2010;Li et al 2012b;van Leeuwen & Timokhin 2012) that the observed state changes on both short and long timescales reflect changes in (1) the global state and energetics of a pulsar's magnetosphere, as implied by the large changes in spin-down rate seen in intermittent pulsars; (2) the accelerating potential directly above the magnetic polar caps (PCs) that generates relativistic particles, as evidenced by mode changes; and (3) the temperature of the hot PC due to particle bombardment as demonstrated by X-ray low and high states that correlate with mode changes. This paper addresses issues in understanding pulsar magnetospheres using the statistical framework of Markov chains:…”
Section: Introductionsupporting
confidence: 79%
See 4 more Smart Citations
“…The ansatz for this paper is consistent with similar ideas expressed by other authors (Ruderman & Sutherland 1975;Cordes 1979Cordes , 1983Jones 1982Jones , 1986Jones , 2011Timokhin 2010;Li et al 2012b;van Leeuwen & Timokhin 2012) that the observed state changes on both short and long timescales reflect changes in (1) the global state and energetics of a pulsar's magnetosphere, as implied by the large changes in spin-down rate seen in intermittent pulsars; (2) the accelerating potential directly above the magnetic polar caps (PCs) that generates relativistic particles, as evidenced by mode changes; and (3) the temperature of the hot PC due to particle bombardment as demonstrated by X-ray low and high states that correlate with mode changes. This paper addresses issues in understanding pulsar magnetospheres using the statistical framework of Markov chains:…”
Section: Introductionsupporting
confidence: 79%
“…This situation applies to an · B < 0 geometry for the OFL region at the NS surface, the situation considered by Ruderman & Sutherland (1975) and Jones (2011Jones ( , 2012Jones ( , 2013, that requires positive charges above the PC. The opposite case with · B > 0 has comparatively uncomplicated electron flows that may not allow pair production and radio emission.…”
Section: Circuit Analogsmentioning
confidence: 99%
See 3 more Smart Citations